2018
DOI: 10.1002/jper.18-0064
|View full text |Cite
|
Sign up to set email alerts
|

A novel U‐shaped relationship between BMI and risk of generalized aggressive periodontitis in Chinese: A cross‐sectional study

Abstract: U-shaped relationships exist between BMI and risk of GAgP, AL, and WBC count in patients with GAgP among Chinese aged below 36 years old with their BMI range from 18 to 28 kg/m ; the optimal BMI value for lowest odds ratio and lowest WBC count of GAgP was 22 kg/m .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…From our previous study, a U–shaped relationship exists between BMI and risk of GAgP and white blood cells (WBC) count. Moreover, WBC counts in patients with GAgP was lowest when the BMI value was 22 kg/m 2 after adjusting for age and gender 24 . However, limited studies report on the effect of BMI on NLR.…”
Section: Discussionmentioning
confidence: 96%
“…From our previous study, a U–shaped relationship exists between BMI and risk of GAgP and white blood cells (WBC) count. Moreover, WBC counts in patients with GAgP was lowest when the BMI value was 22 kg/m 2 after adjusting for age and gender 24 . However, limited studies report on the effect of BMI on NLR.…”
Section: Discussionmentioning
confidence: 96%
“…Some of the major issues associated with PT were the tissue hypoxia, oxidative stress and relative vasospasm which in turn, determines increased coagulation and endothelial injury, damage of vascular endothelial cells, and finally periodontal tissue destruction [ 44 ]. Consequently, some evidence has been suggested that periodontal infection mediated by some pathogens such as A. actinomycetemcomitans may accelerate PT and endothelial damage and inflammatory response orchestrated through oxidative stress pathways [ 45 , 46 ], especially in obese patients [ 47 ]. In this respect, some evidence has shown that the tissue damage associated with PT was due to oxidative stress and, therefore, associated with high levels of nitric oxide (NO) and hs-CRP [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, stepwise multivariate Cox regression analysis was performed to construct a mRNA-derived prognostic model based on the Akaike information criterion (AIC). After calculating the risk score based on the formula of the chosen model, smooth curve fitting was competed to evaluate the relationship between risk score and survival (Li et al, 2019). If a linear relationship between these measures was found, then the cut-off value was set as the median risk score.…”
Section: Methodsmentioning
confidence: 99%